Complex Karyotype is a Stronger Predictor than Del(17p) for Inferior Outcome in Relapsed or Refractory CLL Patients Treated with Ibrutinib-Based Regimens - Thompson, Philip A. (Cancer, 2015)
BACKGROUND: Ibrutinib is active in patients with relapsed/refractory (R/R) CLL. In patients treated with ibrutinib for R/R CLL, del(17p) identified by interphase fluorescence in situ hybridization (FISH) is associated with inferior progression-free survival, despite equivalent initial response rates. Del(17p) is frequently associated with complex metaphase karyotype (CKT); the prognostic significance of CKT in ibrutinib-treated patients has not been reported. METHODS: We reviewed 88 patients treated for R/R CLL at MD Anderson Cancer Center with investigational ibrutinib-based regimens from 2010–2013. Pre-treatment FISH and Lipopolysaccharide-stimulated metaphase cytogenetic analysis were performed on bone marrow. RESULTS: Adequate pre-treatment metaphase karyotype was available for 56/88 patients. Karyotype was complex in 21 of 56 cases; 17 of the 21 had del(17p) by FISH. Overall response rate, including partial remission with persistent lymphocytosis, was 94% with 17% complete responses. In multivariable analysis (MVA), only CKT was significantly associated with event-free survival (EFS) [HR 6.6 (1.7–25.6), p=0.006]. Fludarabine-refractory CLL [HR 6.9 (1.8–27.1), p=0.005] and CKT [HR 5.9 (1.6–22.2), p=0.008] were independently associated with inferior overall survival (OS) in MVA. Del(17p) by FISH was not significantly associated with EFS or OS in MVA. CONCLUSIONS: CKT is a powerful predictor of outcome in ibrutinib-treated patients with R/R CLL and may be a stronger predictor of biological behavior than del(17p) by FISH. Given their relatively poor outcomes, patients with CKT are ideal candidates for studies of consolidative treatment strategies or novel treatment combinations.